Telepathology in India – Revolutionizing Pathology Diagnostics through Digital Innovation - Thusoo, Shweta; Dabholkar, Amita (Journal of Neonatal Surgery, 2025)
With high-resolution imaging, artificial intelligence (AI), and secure telecommunication systems, telepathology, a revolutionary application of digital technology in pathology, enables remote diagnosis, consultation, and second opinions. Telepathology is revolutionizing the diagnostic environment with advances in Whole Slide Imaging (WSI), cloud storage, and AI-based analytics. This is particularly relevant in countries such as India, where access to specialist pathology services is not well distributed. Providing immediate and accurate pathology services is very challenging in India with its sizeable and dispersed populace, especially in remote and rural settings. Though government initiatives such as the National Digital Health Mission (NDHM) have paved the path for enhanced telemedicine facilities, several institutions and healthcare establishments have initiated digital pathology initiatives. The utilization of telepathology in India is still nascent despite such advances. There are still several major hurdles, including the lack of adequate digital infrastructure, prohibitive setup costs, unreliable internet connectivity in outlying areas, and regulatory concerns. In addition, pathologists and laboratory workers must spend a lot of training and change over from the conventional microscopy system to digital pathology. Also necessary are well-crafted regulatory regimes to manage medico-legal and ethical challenges, including data protection and responsibility for diagnosis. This review article discusses the evolution of telepathology, the current situation in India, the challenges to its widespread application, and the potential means of overcoming them. India can bridge the diagnostic gap and ensure that all have access to quality and affordable healthcare by embracing digital pathology innovations and strengthening telehealth regulations.